(untitled) (Al-Qamar, 2022)
Manto highlighted the political, social, economic and psychological problems of his era. Reflected the sentiments of Indians against political oppression and it. Not only did he carry the revolutionary thought of Marxism in his fictions, but he also looked into the eyes of imperialism and did not back down from his position. Lava was boiling in his chest against British imperialism. He had a strong hatred for the capitalist system and class exploitation. His philanthropy is evidenced by the planning in his mind for the eradication of poverty. Minto had no enmity with British imperialism nor was he harassed by the implementation of the new law. Rather, they were against the system behind which the imperialist forces were working, which was poison for the lower classes of the subcontinent. Due to which the economic and economic development of the subcontinent was dependent. By boycotting this imperialist system, Minto proved that the people of the subcontinent wanted real freedom. In which the laborer gets the reward of earning. Slaves are free. They can revolt against oppression and oppression in the face of oppressive and cruel ruler.